KEBERLAKUAN EVALUATIF PENERAPAN PERJANJIAN DIGITAL E-COMMERCE - Imelda Martinelli; Malvin Jati Kuncara Alam (PROSIDING SERINA, 2021)
In legal theory, applicability is divided into three, namely empirical, normative, and evaluative applicability. Evaluative validity is this enforceability exists if the adherents behave according to the legal rules. Legal acts of e-commerce digital agreements are related to legal rules and norms governing them, including agreements and principles that exist between the parties to promise. The agreement begins with an agreement on the contents of the agreement and this agreement is binding on the parties. This means that the parties who are present are normatively bound to the agreement. Furthermore, the arrangement of the agreement is experiencing developments and dynamics in the implementation of the agreement. This is evidenced by the rise of online agreements in the public which are understood by the layman. Therefore, it is necessary to have a simple understanding of the agreement that will help determine the legal consequences, including the rights and obligations of each party. So that each individual will always have legal certainty for the agreed objects. The method of implementing this community service activity is carried out using the lecture, discussion and question and answer method in the Duku RT Block. 10/RW. 10, Cibubur Village, Ciracas District, East Jakarta. The activity begins with material exposure regarding forms of violence, sanctions and prevention. After the presentation, there was a discussion session and a questions and answer session regarding the material that had been presented. The results of the service implementation activities were obtained by understanding various information about evaluative applicability in digital agreements. The output target of this service is an prociding, article and national seminar.